Who owns nature? Sentience, environmental ethics and intervention in nature - Torres Aldave, Mikel (Estudios de Filosofía, 2022)
Who owns nature? The question could be less important than reducing animal sufferings in nature. It does not matter if nature does not belong to anyone (or if it belongs to everybody) or if it belongs to someone, because in both cases there are limitations, linked with animal welfare, regarding what we should do in nature. Sentient beings have interests that we must take into account when designing environmental policies. Since neither ecosystems nor plants have interests, preserving nature is less important than reducing animal sufferings. The relevant moral issue is, therefore, knowing what happens to sentient animals in nature and developing policies to reduce their sufferings. This implies that we have the moral obligation of intervening in nature with the aim of reducing animal sufferings, so conservationist environmental policies defended by ecologists are morally unacceptable.